A method for preparing highly dispersed white carbon black
By using hydrophilic magnesium carbonate and surfactant to form a microemulsion system, combined with ultrasonic shock and heat treatment, the problems of poor dispersion and high hygroscopicity of white carbon black are solved, and the particle size uniformity and purity are improved.
Patent Information
- Application Number
- CN202411281020.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-13
- Publication Date
- 2024-12-13
- Estimated Expiration
- 2044-09-13
AI Technical Summary
The white carbon black prepared by traditional precipitation methods has poor dispersion, uneven particle size, high hygroscopicity, and easy to reduce purity and oil absorption. The existing modification methods are difficult to effectively solve these problems.
Use hydrophilic magnesium carbonate to replace the dispersant magnesium sulfate to form a microemulsion system, increase the dosage of n-butanol and surfactant, and reduce the particle size and hygroscopicity of white carbon black through primary treatment and secondary ultrasonic shock heat treatment, and improve dispersion and purity.
The dispersion, specific surface area and oil absorption value of white carbon black are improved, the particle size distribution is uniform, the hygroscopicity is reduced, and the high purity and oil absorption value are maintained.
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of white carbon black, and in particular to a method for preparing highly dispersed white carbon black. Background Art
[0002] White carbon black mainly refers to precipitated silica, fumed silica and ultrafine silica gel, and also includes powdered synthetic aluminum silicate and calcium silicate. White carbon black is a porous substance, and its composition can be expressed by SiO2·nH2O, where nH2O exists in the form of surface hydroxyl groups. White carbon black is soluble in caustic alkali and hydrofluoric acid, but insoluble in water, solvents and acids (except hydrofluoric acid).
[0003] White carbon black has excellent high temperature resistance and electrical insulation, and is widely used in rubber products, agricultural chemicals, daily chemical products and other fields. The traditional methods for preparing white carbon black include gas phase method and precipitation method. Among them, the gas phase method uses silicon tetrachloride, oxygen (or air) and hydrogen as raw materials, reacts at high temperature to prepare gas phase white carbon black; the precipitation method uses water glass solution and acid as raw materials, and prepares precipitated white carbon black through precipitation, filtration, washing, drying and calcination. Compared with the gas phase method, the precipitation method is simple in preparation method, low in cost, and the prepared precipitated white carbon black has good processability. Therefore, most domestic production enterprises adopt the precipitation method.
[0004] However, the particle size of fumed silica is small, the shape is generally ball-chain-shaped, the surface hydroxyl concentration is low, and the dispersibility is good, while the particle size of precipitated silica is large, the shape is generally spherical, the surface hydroxyl concentration is high, and the dispersibility is poor. The main reason is that when preparing silica by precipitation method, the raw material water glass used is a tetrahedral structure with -ONa at the vertex. After the water glass reacts with acid, the -ONa at the vertex is converted into -OH to generate silica gel. Silica gel is a particle with a large specific surface area and a large amount of water adsorbed on its surface. The presence of water hinders the combination of O and Si in the vertex. If water is lost, O and Si in the vertex will quickly combine and quickly grow into coarse particles with uneven particle size distribution, reducing surface activity. In addition, some O in the vertices are not combined with Si and still exist in the form of -OH, that is, they still exist in the form of hydroxyl, resulting in a high surface hydroxyl concentration of precipitated silica, thereby reducing the dispersibility of precipitated silica.
[0005] In order to solve the above problems, the most commonly used method is to perform surface modification on precipitated silica or to add n-butanol in the preparation of precipitated silica. Specifically, the surface modification of precipitated silica is to use a silane coupling agent to perform surface modification on precipitated silica; n-butanol is added in the preparation of precipitated silica, specifically, water glass solution is mixed with n-butanol and a dispersant, and then an acid is added to react. On the one hand, n-butanol can form hydrogen bonds with the O at the vertices of the water glass, thereby playing an isolating role and avoiding the combination of the O at the vertices with Si. On the other hand, n-butanol can form an azeotrope with water, thereby removing the water in the precipitated silica and reducing the surface hydroxyl concentration.
[0006] However, surface modification of precipitated silica has the following problems: first, it will reduce the purity of precipitated silica; second, since precipitated silica is easy to agglomerate to form aggregates, it is difficult for silane coupling agents to enter the interior of the aggregates for surface modification, resulting in uneven surface modification, which further leads to uneven particle size distribution. The precipitated silica obtained by adding n-butanol in the preparation of precipitated silica contains a small amount of n-butanol. The presence of n-butanol will increase the hygroscopicity of precipitated silica, deteriorate storage resistance, and reduce the oil absorption value.
[0007] Therefore, it is an urgent problem to study a preparation method of silica to improve the dispersibility of silica while reducing the particle size and hygroscopicity of silica to ensure that the particle size distribution of silica is uniform and the purity and oil absorption value are not reduced. Summary of the invention
[0008] In view of the shortcomings of the prior art, the present invention provides a method for preparing highly dispersible white carbon black, which can improve the dispersibility of white carbon black, reduce the particle size and hygroscopicity of white carbon black, and ensure that the particle size distribution of white carbon black is uniform, and the purity and oil absorption value are not reduced.
[0009] In order to solve the above technical problems, the technical solution adopted by the present invention is as follows:
[0010] A method for preparing highly dispersible white carbon black, comprising the following steps: preparing hydrophilic magnesium carbonate, preparing a reaction solution, preparing a mixed solution, reacting, primary treatment, and secondary treatment;
[0011] The method for preparing the hydrophilic magnesium carbonate comprises: mixing magnesium carbonate, anhydrous ethanol, 3-aminopropyltriethoxysilane and deionized water, stirring at 40-45° C. at a stirring speed of 100-200 rpm for 9-10 hours, centrifuging at a centrifugal speed of 8000-9000 rpm for 5-6 minutes, taking a precipitate, washing the precipitate with anhydrous ethanol, and vacuum drying to obtain the hydrophilic magnesium carbonate;
[0012] In the preparation of the hydrophilic magnesium carbonate, after the magnesium carbonate and anhydrous ethanol are mixed, the mass ratio of 3-aminopropyltriethoxysilane and deionized water is 18-20:6000-6500:20-25:400-500;
[0013] The D50 particle size of the magnesium carbonate is 2 μm;
[0014] The method for preparing the reaction liquid is: after mixing the water glass aqueous solution and the hydrophilic magnesium carbonate, stirring at 40-45° C. and a stirring speed of 100-200 rpm for 30-35 minutes to obtain the reaction liquid;
[0015] In the preparation reaction solution, the mass ratio of water glass aqueous solution to hydrophilic magnesium carbonate is 5500-6000:90-100;
[0016] The mass concentration of the water glass aqueous solution is 8%;
[0017] The modulus of the water glass is 2.5;
[0018] The method for preparing the mixed solution is to mix the reaction solution, hexadecyltrimethylammonium chloride and n-butanol, and stir at room temperature at a stirring speed of 300-400 rpm for 40-45 minutes to obtain a mixed solution;
[0019] In the prepared mixed solution, the mass ratio of the reaction solution, hexadecyltrimethylammonium chloride and n-butanol is 700-750:2400-2600:7000-8000;
[0020] The reaction method comprises heating the mixed solution to 70-80° C. and stirring at a stirring speed of 100-200 rpm, then dropping a sulfuric acid aqueous solution until the pH value of the reaction system is 8-9, continuing stirring for 60-80 minutes after the dropping is completed, then dropping concentrated sulfuric acid until the pH value of the reaction system is 4-5, stopping stirring after the dropping is completed, and standing for 40-60 minutes to obtain a white carbon black dispersion;
[0021] The mass concentration of the sulfuric acid aqueous solution is 20%, and the dropping speed is 2-3g / min;
[0022] The mass concentration of the concentrated sulfuric acid is 98%, and the dropping speed is 1-2g / min;
[0023] The method of the one-time treatment is to distill the white carbon black dispersion at 100-105° C., filter, and heat-treat the filter residue to obtain the one-time treated white carbon black;
[0024] In the primary treatment, the heat treatment is to heat the filter residue to 100-105°C at a heating rate of 2-3°C, keep the temperature for 50-60min, then heat the residue to 220-230°C at a heating rate of 2-3°C, and keep the temperature for 50-60min;
[0025] The secondary treatment method comprises mixing the primary treated white carbon black and glacial acetic acid, performing ultrasonic vibration, filtering, and taking the filter residue for heat treatment to obtain highly dispersed white carbon black;
[0026] The mass ratio of the mixed solution in the reaction to the glacial acetic acid in the secondary treatment is 5000-5500:100-120;
[0027] In the secondary treatment, the heat treatment is to heat the filter residue to 117-120°C at a heating rate of 2-3°C / min, keep the temperature for 50-60min, then heat the residue to 220-230°C at a heating rate of 2-3°C / min, and keep the temperature for 50-60min;
[0028] The frequency of the ultrasonic oscillation is 25-30kHz, and the duration is 30-40min.
[0029] Compared with the prior art, the present invention has the following beneficial effects:
[0030] (1) The method for preparing highly dispersible white carbon black of the present invention increases the dosage of n-butanol and surfactant on the basis of the prior art to form a microemulsion system to promote dispersion, thereby improving the dispersibility, specific surface area, purity and oil absorption value of the prepared white carbon black, reducing the particle size of the prepared white carbon black, and ensuring that the particle size distribution of the prepared white carbon black is uniform; the present invention also uses hydrophilic magnesium carbonate to replace the dispersant magnesium sulfate. On the one hand, the hydrophilic magnesium carbonate can promote the formation of the microemulsion system; on the other hand, the hydrophilic magnesium carbonate can promote the uniform dispersion of the reactants; on the third hand, during the reaction, magnesium carbonate reacts with sulfuric acid to gradually and evenly release carbon dioxide, thereby promoting the reaction and reducing the excessive growth of silicon dioxide during the reaction. The dispersibility, specific surface area, purity and oil absorption value of the prepared white carbon black are improved, the particle size of the prepared white carbon black is reduced, and the particle size distribution of the prepared white carbon black is ensured to be uniform; the present invention also adds a secondary treatment step, specifically, after mixing glacial acetic acid with the once-treated white carbon black, ultrasonic vibration is performed, and then heat treatment is performed. During the ultrasonic vibration process, the hydrogen bond between the remaining n-butanol and the hydroxyl group is broken, and the n-butanol and glacial acetic acid undergo an esterification reaction to generate n-butanol ethyl ester, and hydrogen bonds are formed between the glacial acetic acid and the released hydroxyl groups. Then, during the heat treatment, the volatility of glacial acetic acid is utilized to accelerate the removal of the remaining hydroxyl groups in the white carbon black, that is, water, thereby further reducing the impurity content in the white carbon black, improving the purity, dispersibility and oil absorption value of the white carbon black, and reducing the hygroscopicity of the white carbon black;
[0031] (2) The method for preparing highly dispersible white carbon black of the present invention can improve the dispersibility of white carbon black, and the dispersibility of the prepared white carbon black is 9.5;
[0032] (3) The method for preparing highly dispersed white carbon black of the present invention can reduce the particle size of white carbon black and ensure that the particle size distribution of white carbon black is uniform. The D50 particle size of the prepared white carbon black is 151-164 μm, and the D90 particle size is 207-218 μm.
[0033] (4) The method for preparing highly dispersed white carbon black of the present invention can reduce the particle size of white carbon black and ensure that the particle size distribution of white carbon black is uniform. The D50 particle size of the prepared white carbon black is 151-164 μm, the D90 particle size is 207-218 μm, and the BET specific surface area is 382-395 m 2 / g;
[0034] (5) The method for preparing highly dispersed white carbon black of the present invention can ensure that the purity of the white carbon black does not decrease, and the purity of the prepared white carbon black is 90.7-91.5%;
[0035] (6) The method for preparing highly dispersible white carbon black of the present invention can ensure that the oil absorption value of the white carbon black does not decrease, and the oil absorption value of the prepared white carbon black is 3.2-3.3 cm 3 / g;
[0036] (7) The method for preparing highly dispersed white carbon black of the present invention can reduce the hygroscopicity of white carbon black. When the method for preparing highly dispersed white carbon black of the present invention is placed in an environment with a temperature of 30° C. and a relative humidity of 70% for 5 days, no agglomeration occurs. DETAILED DESCRIPTION
[0037] In order to have a clearer understanding of the technical features, purposes and effects of the present invention, the specific implementation methods of the present invention are now described.
[0038] Example 1
[0039] A method for preparing highly dispersible white carbon black, specifically comprising:
[0040] 1. Preparation of hydrophilic magnesium carbonate: 18 g of magnesium carbonate, 6000 g of anhydrous ethanol, 20 g of 3-aminopropyltriethoxysilane, and 400 g of deionized water were mixed, stirred at 40° C. at a stirring speed of 100 rpm for 9 h, centrifuged at a centrifugal speed of 8000 rpm for 5 min, and the precipitate was taken, washed with anhydrous ethanol, and vacuum dried to obtain hydrophilic magnesium carbonate;
[0041] The D50 particle size of the magnesium carbonate is 2 μm;
[0042] 2. Prepare a reaction solution: Mix 5500 g of water glass aqueous solution and 90 g of hydrophilic magnesium carbonate, and stir at 40° C. at a stirring speed of 100 rpm for 30 min to obtain a reaction solution;
[0043] The mass concentration of the water glass aqueous solution is 8%;
[0044] The modulus of the water glass is 2.5;
[0045] 3. Prepare a mixed solution: mix 700 g of the reaction solution, 2400 g of hexadecyltrimethylammonium chloride and 7000 g of n-butanol, and stir at room temperature at a stirring speed of 300 rpm for 40 min to obtain a mixed solution;
[0046] 4. Reaction: Heat 5000g of the mixed solution to 70°C and stir at a stirring speed of 100rpm, then add sulfuric acid aqueous solution until the pH of the reaction system is 8, continue stirring for 60min after the addition, then add concentrated sulfuric acid until the pH of the reaction system is 4, stop stirring after the addition, and let stand for 40min to obtain a white carbon black dispersion;
[0047] The mass concentration of the sulfuric acid aqueous solution is 20%, and the dropping speed is 2g / min;
[0048] The mass concentration of the concentrated sulfuric acid is 98%, and the dropping speed is 1g / min;
[0049] 5. Primary treatment: distill the white carbon black dispersion obtained in step 4 at 100°C, filter, take the filter residue, heat the filter residue to 100°C at a heating rate of 2°C, keep it warm for 50 minutes, then heat it to 220°C at a heating rate of 2°C, keep it warm for 50 minutes, and obtain the primary treated white carbon black;
[0050] 6. Secondary treatment: Mix the once-treated white carbon black obtained in step 5 with 100 g of glacial acetic acid, and ultrasonically vibrate at a frequency of 25 kHz for 30 min. Filter and take the filter residue. Heat the filter residue to 117°C at a heating rate of 2°C / min, keep it warm for 50 min, and then heat it to 220°C at a heating rate of 2°C / min, and keep it warm for 50 min to obtain highly dispersed white carbon black.
[0051] Example 2
[0052] A method for preparing highly dispersible white carbon black, specifically comprising:
[0053] 1. Preparation of hydrophilic magnesium carbonate: 19 g of magnesium carbonate, 6200 g of anhydrous ethanol, 22 g of 3-aminopropyltriethoxysilane, and 450 g of deionized water were mixed, stirred at 42 ° C at a stirring speed of 150 rpm for 9.5 h, centrifuged at a centrifugal speed of 8500 rpm for 6 min, and the precipitate was taken, washed with anhydrous ethanol, and vacuum dried to obtain hydrophilic magnesium carbonate;
[0054] The D50 particle size of the magnesium carbonate is 2 μm;
[0055] 2. Prepare a reaction solution: Mix 5800 g of water glass aqueous solution and 95 g of hydrophilic magnesium carbonate, and stir at 42° C. at a stirring speed of 150 rpm for 35 min to obtain a reaction solution;
[0056] The mass concentration of the water glass aqueous solution is 8%;
[0057] The modulus of the water glass is 2.5;
[0058] 3. Prepare a mixed solution: mix 720 g of the reaction solution, 2500 g of hexadecyltrimethylammonium chloride, and 7500 g of n-butanol, and stir at room temperature at a stirring speed of 350 rpm for 45 min to obtain a mixed solution;
[0059] 4. Reaction: Heat 5200g of the mixed solution to 75°C and stir at a stirring speed of 150rpm, then add sulfuric acid aqueous solution until the pH of the reaction system is 8.5, continue stirring for 70min after the addition, then add concentrated sulfuric acid until the pH of the reaction system is 4.5, stop stirring after the addition, and let stand for 50min to obtain a white carbon black dispersion;
[0060] The mass concentration of the sulfuric acid aqueous solution is 20%, and the dropping speed is 2.5g / min;
[0061] The mass concentration of the concentrated sulfuric acid is 98%, and the dropping speed is 1.5 g / min;
[0062] 5. Primary treatment: distill the white carbon black dispersion obtained in step 4 at 102°C, filter, take the filter residue, heat the filter residue to 102°C at a heating rate of 2.5°C, keep it warm for 55 minutes, then heat it to 225°C at a heating rate of 2.5°C, keep it warm for 55 minutes, and obtain the primary treated white carbon black;
[0063] 6. Secondary treatment: Mix the once-treated white carbon black obtained in step 5 with 110 g of glacial acetic acid, ultrasonically vibrate at a frequency of 30 kHz for 35 minutes, filter, take the filter residue, heat the filter residue to 118°C at a heating rate of 2.5°C / min, keep it warm for 55 minutes, then heat it to 225°C at a heating rate of 2.5°C / min, keep it warm for 55 minutes, and obtain highly dispersed white carbon black.
[0064] Example 3
[0065] A method for preparing highly dispersible white carbon black, specifically comprising:
[0066] 1. Preparation of hydrophilic magnesium carbonate: 20 g of magnesium carbonate, 6500 g of anhydrous ethanol, 25 g of 3-aminopropyltriethoxysilane, and 500 g of deionized water were mixed, stirred at 45 ° C at a stirring speed of 200 rpm for 10 h, centrifuged at a centrifugal speed of 9000 rpm for 6 min, and the precipitate was taken, washed with anhydrous ethanol, and vacuum dried to obtain hydrophilic magnesium carbonate;
[0067] The D50 particle size of the magnesium carbonate is 2 μm;
[0068] 2. Prepare a reaction solution: Mix 6000 g of water glass aqueous solution and 100 g of hydrophilic magnesium carbonate, and stir at 45° C. at a stirring speed of 200 rpm for 35 min to obtain a reaction solution;
[0069] The mass concentration of the water glass aqueous solution is 8%;
[0070] The modulus of the water glass is 2.5;
[0071] 3. Prepare a mixed solution: mix 750 g of the reaction solution, 2600 g of hexadecyltrimethylammonium chloride and 8000 g of n-butanol, and stir at room temperature at a stirring speed of 400 rpm for 45 min to obtain a mixed solution;
[0072] 4. Reaction: Heat 5500g of the mixed solution to 80°C and stir at a stirring speed of 200rpm, then add sulfuric acid aqueous solution until the pH of the reaction system is 9, continue stirring for 80min after the addition, then add concentrated sulfuric acid until the pH of the reaction system is 5, stop stirring after the addition, and let stand for 60min to obtain a white carbon black dispersion;
[0073] The mass concentration of the sulfuric acid aqueous solution is 20%, and the dropping speed is 3g / min;
[0074] The mass concentration of the concentrated sulfuric acid is 98%, and the dropping speed is 2g / min;
[0075] 5. Primary treatment: distill the white carbon black dispersion obtained in step 4 at 105°C, filter, take the filter residue, heat the filter residue to 105°C at a heating rate of 3°C, keep it warm for 60 minutes, then heat it to 230°C at a heating rate of 3°C, keep it warm for 60 minutes, and obtain the primary treated white carbon black;
[0076] 6. Secondary treatment: Mix the once-treated white carbon black obtained in step 5 with 120 g of glacial acetic acid, and ultrasonically vibrate at a frequency of 30 kHz for 40 min. Filter and take the filter residue. Heat the residue to 120°C at a heating rate of 3°C / min, keep it warm for 60 min, and then heat it to 230°C at a heating rate of 3°C / min, and keep it warm for 60 min to obtain highly dispersed white carbon black.
[0077] Comparative Example 1
[0078] Based on the preparation method of highly dispersed silica in Example 1, the first step of preparing hydrophilic magnesium carbonate is omitted, and in the second step of preparing the reaction solution, 64 g of magnesium sulfate is used instead of 90 g of hydrophilic magnesium carbonate.
[0079] Comparative Example 2
[0080] On the basis of the preparation method of highly dispersed silica in Example 1, the secondary treatment step in step 6 is omitted, that is, the once-treated silica obtained in the primary treatment step in step 5 is directly used as highly dispersed silica.
[0081] Comparative Example 3
[0082] According to the method of preparing highly dispersed white carbon black in Chinese patent CN113753905B, the highly dispersed white carbon black is prepared as follows:
[0083] 1. Dissolution: Dissolve water glass and sodium sulfate in water to obtain a reaction base solution;
[0084] The modulus of the water glass is 2.5;
[0085] The mass concentration of the water glass is 6%, and the mass concentration of the sodium sulfate is 0.8%;
[0086] 2. Mixing: Mix n-butanol, sodium citrate and reaction base solution to obtain a mixed solution;
[0087] The volume ratio of n-butanol to reaction base liquid is 1:1;
[0088] The mass concentration of sodium citrate in the mixed solution is 0.2%;
[0089] 3. Reaction: sulfuric acid with a molar concentration of 2.5 mol / L was added dropwise to the mixed solution, and alkaline gas was introduced at a flow rate of 80 L / s for reaction. During the reaction, the temperature of the mixed solution was maintained at 70°C, the stirring speed was 100 rpm, the pH was 10.5, and the reaction time was 80 min. After the reaction, sulfuric acid with a molar concentration of 2.5 mol / L was continued to be added dropwise until the pH value was 4.5, and the mixture was allowed to stand for 40 min to obtain a white carbon black dispersion;
[0090] The alkaline gas is a mixed gas of ammonia and nitrogen, wherein the volume concentration of ammonia is 15%;
[0091] 4. Treatment: Distill the silica dispersion at 100°C and filter it, take the filter residue, heat the residue to 100°C at a heating rate of 2°C / min, keep it warm for 50 minutes, then heat it to 220°C at a heating rate of 2°C / min, keep it warm for 50 minutes, and obtain highly dispersed silica.
[0092] Performance Test 1
[0093] The dispersion degree, D50 particle size, D90 particle size, BET specific surface area, purity and oil absorption value of the highly dispersed white carbon black obtained in Examples 1-3 and Comparative Examples 1-2 were tested, and the test results are as follows:
[0094]
[0095] Performance Test 2
[0096] The highly dispersed white carbon black obtained in Examples 1-3 and Comparative Examples 1-2 were respectively placed in an environment with a temperature of 30° C. and a relative humidity of 70% and left to stand for 5 days, and then observed whether there was agglomeration. The results were as follows:
[0097]
[0098] It can be seen from the above results that the preparation method of highly dispersible white carbon black of Examples 1-3 can improve the dispersion of white carbon black, reduce the particle size and hygroscopicity of white carbon black, and ensure that the particle size distribution of white carbon black is uniform, and the purity and oil absorption value are not reduced;
[0099] In the preparation method of highly dispersible white carbon black of Comparative Example 1, hydrophilic magnesium carbonate is not added, resulting in low dispersion, large particle size, uneven particle size distribution, small BET specific surface area, low purity, and low oil absorption value of the prepared white carbon black;
[0100] In the preparation method of highly dispersible white carbon black in Comparative Example 2, the white carbon black treated once was not subjected to secondary treatment, resulting in low dispersion, low purity, low oil absorption value and high hygroscopicity of the prepared white carbon black;
[0101] The preparation method of the highly dispersed silica in Comparative Example 3 is different from the preparation method of the highly dispersed silica in Examples 1-3, resulting in the prepared silica having low dispersion, large particle size, uneven particle size distribution, small BET specific surface area, low purity, low oil absorption value, and high hygroscopicity.
[0102] Unless otherwise specified, all percentages used in the present invention are by mass.
[0103] Finally, it should be noted that the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art can still modify the technical solutions described in the aforementioned embodiments or replace some of the technical features therein by equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A method for preparing highly dispersible white carbon black, characterized in that: The method comprises the following steps: preparing hydrophilic magnesium carbonate, preparing a reaction solution, preparing a mixed solution, reacting, a primary treatment, and a secondary treatment; The method for preparing hydrophilic magnesium carbonate comprises mixing magnesium carbonate, anhydrous ethanol, 3-aminopropyltriethoxysilane and deionized water, stirring at 40-45° C. for 9-10 hours, centrifuging, taking a precipitate, washing and vacuum drying the precipitate to obtain hydrophilic magnesium carbonate; The method for preparing the reaction solution is to mix a water glass aqueous solution and a hydrophilic magnesium carbonate, and then stir the mixture at 40-45° C. for 30-35 minutes to obtain a reaction solution; The method for preparing the mixed solution is to mix the reaction solution, hexadecyltrimethylammonium chloride and n-butanol, and stir at room temperature for 40-45 minutes to obtain a mixed solution; The reaction method comprises heating the mixed solution to 70-80° C., stirring, then dripping a sulfuric acid aqueous solution until the pH value of the reaction system is 8-9, continuing to stir for 60-80 minutes after the dripping, then dripping concentrated sulfuric acid until the pH value of the reaction system is 4-5, stopping stirring after the dripping, and standing for 40-60 minutes to obtain a white carbon black dispersion; The method of the one-time treatment is to distill the white carbon black dispersion at 100-105° C., filter, and heat-treat the filter residue to obtain the one-time treated white carbon black; The secondary treatment method comprises mixing the primary treated white carbon black and glacial acetic acid, performing ultrasonic vibration, filtering, and taking the filter residue for heat treatment to obtain highly dispersed white carbon black.
2. The method for preparing highly dispersible white carbon black according to claim 1, characterized in that: In the preparation of the hydrophilic magnesium carbonate, the mass ratio of magnesium carbonate, anhydrous ethanol, 3-aminopropyltriethoxysilane and deionized water is 18-20:6000-6500:20-25:400-500; The D50 particle size of the magnesium carbonate is 2 μm.
3. The method for preparing highly dispersible white carbon black according to claim 1, characterized in that: In the preparation reaction solution, the mass ratio of water glass aqueous solution to hydrophilic magnesium carbonate is 5500-6000:90-100; The mass concentration of the water glass aqueous solution is 8%; The modulus of the water glass is 2.
5.
4. The method for preparing highly dispersible white carbon black according to claim 1, characterized in that: In the prepared mixed solution, the mass ratio of the reaction solution, hexadecyltrimethylammonium chloride and n-butanol is 700-750:2400-2600:7000-8000; The mass concentration of the sulfuric acid aqueous solution is 20%, and the dropping speed is 2-3g / min; The mass concentration of the concentrated sulfuric acid is 98%, and the dropping speed is 1-2 g / min.
5. The method for preparing highly dispersible white carbon black according to claim 1, characterized in that: In the one-time treatment, the heat treatment is to heat the filter residue to 100-105°C at a heating rate of 2-3°C, keep the temperature for 50-60 minutes, then heat the residue to 220-230°C at a heating rate of 2-3°C, and keep the temperature for 50-60 minutes.
6. The method for preparing highly dispersible white carbon black according to claim 1, characterized in that: The mass ratio of the mixed solution in the reaction to the glacial acetic acid in the secondary treatment is 5000-5500:100-120.
7. The method for preparing highly dispersible white carbon black according to claim 1, characterized in that: In the secondary treatment, the heat treatment is to heat the filter residue to 117-120°C at a heating rate of 2-3°C / min, keep the temperature for 50-60min, then heat the residue to 220-230°C at a heating rate of 2-3°C / min, and keep the temperature for 50-60min; The frequency of the ultrasonic oscillation is 25-30kHz, and the duration is 30-40min.
